2012
DOI: 10.7439/ijbar.v3i7.511
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine as an adjuvant in supraclavicular brachial plexus block.

Abstract: Background & Aims: Brachial plexus block is a useful alternative to general anaesthesia. Postoperative analgesia is an added advantage. Buprenorphine, an agonist antagonist opioid has been used by various routes to prolong analgesia. The present study was undertaken to assess the analgesic efficacy of Buprenorphine with Bupivacaine in brachial plexus block. Methods: A prospective, randomized, double blind study was done on 60 adult patients of American Society of Anesthesiologists 1 and 2, aged between 18-50 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Singam et al . [ 17 ] reported the total duration of sensory block and motor block when 2 ml (0.3 mg) buprenorphine was added to the local anesthetic and then used for supraclavicular block as 647.83 ± 55.70 min and 306.33 ± 20.12 min, respectively, which is quite close to the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Singam et al . [ 17 ] reported the total duration of sensory block and motor block when 2 ml (0.3 mg) buprenorphine was added to the local anesthetic and then used for supraclavicular block as 647.83 ± 55.70 min and 306.33 ± 20.12 min, respectively, which is quite close to the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…From 2001 onward, eight studies[ 5 6 7 8 9 10 13 14 ] have reported significantly long duration of analgesia using buprenorphine in brachial plexus block. However, only three[ 6 10 13 ] out of eight studies had systemic control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, only three[ 6 10 13 ] out of eight studies had systemic control group. Rest five studies[ 5 7 8 9 14 ] had placebo control group where plain LAs were used for the block. In 2008, Jadon et al [ 13 ] studied the effect of the addition of 3 μg/kg buprenorphine to 0.3% bupivacaine in subclavian perivascular block.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations